2017
DOI: 10.25124/jmi.v16i2.315
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh E-Wom Terhadap Keputusan Berkunjung Ke Tempat Wisata Di Kota Bandung

Abstract: AbstrakBerwisata sudah menjadi bagian dari kebutuhan sebagian masyarakat di Indonesia. Seiring dengan meningkatnya minat masyarakat Indonesia berwisata, maka industri parawisata pun mengalami perubahan pesat. Berbagai peluang usaha di bidang jasa pariwisata pun mulai merambah, seperti pemesanan tiket, akomodasi, hingga alternatif pilihan perjalanan seperti buku, blog, sosial media, layanan jasa informasi, hingga pengalaman yang didapat dari orang lain. Hal ini dilakukan agar penggemar kegiatan wisata mempunyai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 2 publications
0
7
0
9
Order By: Relevance
“…Majority of residents gather information through the internet including for reference tourist destinations. Several issues on e-wom based on the research of Mustikasari & Widaningsih (2016) were the intensity, content, and valence of opinion. To Sari & Pangestuti (2018) research, shows that e-wom has links with decision stay.…”
Section: The Relation Of Variable Attribute Tourism Products On the Dmentioning
confidence: 99%
“…Majority of residents gather information through the internet including for reference tourist destinations. Several issues on e-wom based on the research of Mustikasari & Widaningsih (2016) were the intensity, content, and valence of opinion. To Sari & Pangestuti (2018) research, shows that e-wom has links with decision stay.…”
Section: The Relation Of Variable Attribute Tourism Products On the Dmentioning
confidence: 99%
“…Hal tersebut didukung oleh beberapa penelitian yang telah dilakukan sebelumnya, salah satunya adalah penelitian oleh (Mustikasari & Widaningsih, 2016), (Maulidi & Pangestuti, 2019), (Sari et al, 2019) dengan judul Pengaruh e-wom terhadap minat pengunjung dan keputusan berkunjung menyatakan bahwa hubungan masing-masing variabel memiliki hasil signifikan positif.…”
Section: Pendahuluanunclassified
“…The rapid development of communication media, especially social media, makes it easier for tourists to share positive or negative impressions and stories that have been felt while traveling (Giam & Megawati, 2019). (Mustikasari & Widaningsih, 2016), stated that the World Tourism Organization revealed that around 95% of web users use the internet to collect information related to tourism and 93% visit tourism websites when planning a vacation. According to (Hapsari et al, 2021)that before a tourist travels, they will first seek information about the tourist attraction to be visited one of the sources of information an electronic word of mouth.…”
Section: Introductionmentioning
confidence: 99%